Сто великих политиков - Соколов Борис Вадимович (100 великих, 2010)
На обл. авт. не указан Экземпляры: (20161107) / Инвентарный номер: 542zz / Цена: / Сис.шифр: 63.3(0)-8 / Авт.знак: С 59 / ББК: 63.3(0)-8